Effect of digoxin on corrected QT interval in geriatric inpatients: a prospective observational study - Lozano, Roberto; Bona, Carina (International Journal of Basic & Clinical Pharmacology, 2025)
Background: QT interval prolongation is a recognized surrogate marker for torsades de pointes risk. Digoxin, a cardiac glycoside used for atrial fibrillation and heart failure, is not typically associated with torsades but may shorten QTc, particularly in toxicity. Whether therapeutic digoxin shortens QTc in elderly inpatients remains unclear. Objective was to evaluate the effect of digoxin on QTc interval in geriatric inpatients at therapeutic plasma concentrations. Methods: We performed a prospective observational study over six months (November 2012-February 2013) in 201 geriatric inpatients. QT intervals were measured ≥15 days after digoxin initiation and corrected using Bazett’s (QTcB) and Fridericia’s (QTcF) formulas. Patients on amiodarone, donepezil, salbutamol, or venlafaxine were excluded. Covariates included demographics, comorbidities (hypertension, heart failure, diabetes, renal disease, atrial fibrillation/flutter, COPD), and clinical presentation. High QTc was defined as >460 ms in women and >450 ms in men. Results: Twenty-three patients received digoxin (mean dose 151±88 µg/day; mean plasma level 1.2±0.4 ng/ml) and 152 served as controls. Digoxin patients had lower QTcB (427.7±33.5 ms versus 447.1±56.2 ms; p=0.1166) and QTcF (408.4±36.1 ms versus 423.2±48.5 ms; p=0.1642). High QTc prevalence was lower in the digoxin group for QTcB (13.0% versus 28.9%, p=0.082) and QTcF (8.7% versus 23.0%, p=0.162), though differences were not statistically significant. Baseline characteristics were otherwise similar between groups. Conclusions: In elderly inpatients, digoxin therapy was associated with a non-significant trend toward QTc shortening and lower prevalence of high QTc. These findings do not support initiating digoxin solely to reduce QTc but suggest a potential ancillary benefit in patients already indicated for the drug. Larger studies at higher therapeutic plasma levels are warranted.